Serum 25(OH)D reflects clinical characterization in dogs with chronic enteropathies - Vecchiato, Carla Giuditta; Bardhi, Anisa; Tardo, Antonio Maria; Foietta, Lorenzo; Biagi, Giacomo; Sabetti, Maria Chiara; Fracassi, Federico; Barbarossa, Andrea; Pietra, Marco (Frontiers in Veterinary Science, 2025)
IntroductionIn canine chronic enteropathies (CE) and protein-losing enteropathy (PLE), vitamin D deficiency is recognized as a negative prognostic factor, while 25(OH)D status in relation to other clinical phenotypes has been poorly investigated.MethodsThis study aimed to describe differences in CE dogs according to their response to treatment and to reveal potential associations with retrospective clinical and diagnostic data.ResultsA total of 91 dogs were obtained from clinical records and categorized based on their response to treatment into the following groups: food-responsive enteropathy (FRE, n = 39), microbiota-related modulation-responsive enteropathies (MrMRE, n = 26), immunosuppressant-responsive enteropathy (IRE, n = 16), and PLE (n = 10). 25(OH)D, determined by UHPLC–MS/MS from stored serum samples, differed significantly among groups (p < 0.001). Median levels were markedly lower in the PLE group (10.3 ng/mL; range 10–27) than in FRE (33 ng/mL; 10–68) and MrMRE (37 ng/mL; 10–61) groups (p < 0.001). IRE group (20 ng/mL; 10–43) also showed reduced concentrations relative to FRE and MrMRE (p = 0.006). A multivariable linear regression model obtained using data from 75/91 dogs, revealed that fructosamine and phosphorus were positively associated with 25(OH)D status, while increased c-reactive protein was associated with a lower 25(OH)D.ConclusionIn CE dogs, 25(OH)D is negatively affected by inflammation and reflects the severity of clinical characteristics and serum protein-related biomarkers.